Menemukan Kalimat Perintah Di Sekolah Dasar: Memanfaatkan Kalimat Perintah Pada Kumpulan Cerita Pendek Pulpen - Melania Erlinda; Widjojoko; Deni Wardana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Indonesian is the language used as a unifying language. In addition, in elementary schools Indonesian is also one of the subjects. One of the materials studied is sentences. Of the various types of sentences, the sentence that will be discussed further is the imperative sentence. Although this sentence is very common in the practice of everyday life. But not everyone has full knowledge of what a command sentence is. Therefore, this study aims to find out, analyze and describe the imperative sentences in the collection of short stories Pen, and use them as teaching materials to find imperative sentences in grade II elementary school. This study uses a qualitative approach with content analysis method. Then use a collection technique, namely technical document analysis which is then analyzed through three stages consisting of data reduction, data presentation and drawing conclusions. The results of this study, found imperative sentences in 13 stories in the collection of short stories Pen by 26 special intelligent children. The command sentences are 60 sentences and have been validated by experts. In the collection of short stories Pen, there are three types of command sentences, namely the actual command sentence totaling 34 sentences, the invitation-to-command sentence totaling 22 sentences and the prohibition command sentence totaling 4 sentences. Then the results of the analysis of command sentences in a collection of short stories Pens are used as an alternative to writing teaching materials to find imperative sentences in grade II elementary school.